Firm growth: Adjustment and fluctuations - Paavo Peisa (Bank of Finland, 1988)
Firm growth is analysed using panel data for a sample of Finnish firms over the period 1978 - 1985. The paper focuses on the relationship between firm characteristics and growth, paying attention to both latent and measured characteristics. Estimation results indicate that small firms grew significantly faster than large firms during the sample period. Small businesses expanded during the first years of the sample period, whereas later on there were no differences in performance between different size groups.
URN:NBN:fi:bof-201807301748
Keywords: 330